THE EFFECT OF SPECIAL PRICE GIVING ON THE LAMPUNG POST DAILY NEWSPAPER ON COLLEGE STUDENTS BUYING INTEREST IN BANDAR LAMPUNG (A Study Case at students of IBI Darmajaya) - -, Zuriana (Prosiding International conference on Information Technology and Business (ICITB), 2015)
The effort of marketing strategies are meant tomaintain the compnay life, so it is necessary todetermine the right marketing strategies in order thatthe market segment of the Lampung Post dailynewspaper (SKH Lampung Post) can be maintainedor increased. The Lampung Post needs to determinethe right marketing strategies to maintain the marketsegment.The formulation of the problem in the research iswhether the special price on the Lampung Post has aneffect on the buying interest of the students of IBIDarmajaya Bandar Lampung. The research is aimedat measuring how much the special price on theLampung Post affect the buying interest of thestudents of IBI Darmajaya Bandar Lampung. Themethod used in the research is descriptive and thetype of the research is associative. The population isall students of IBI Darmajaya as 2167 students, thenthe sample is taken as 96 respondents.The result of regression equation obtained isY=0,218+1,380X which means that special pricevariable (X) has a positive effect on the buyinginterest with regression coefficient as 1.380 meaningthat if the special price variable increase 1, so thebuying interest will increase as 1.380. there is apositive and significant effect of special price on theLampung Post (X) on buying interest of the studentsod IBI Darmajaya because tcount > ttable ((7,998)>t table(1,662) nilai sig 0,000 < 0,05.KEY WORDS : Price strategy, buying interest